Designing IoT-Based Brackish Water Desalination Equipment to Meet Drinking Water Needs in Coastal Areas - Rimbawati - Rimbawati; Darwin Darwin; Rahmanda Syahputra; Almira Amir; Dultudes Mangopo (Universitas Islam Sumatera Utara, 2026)
Water is one of the main sources that are very important for the needs of living beings. Water that has too high salinity can cause harm if used for certain activities, for example, it is harmful to health when used as drinking water, causing crop failure for agriculture, corrosion of equipment and buildings made of metal elements. The process of treating brackish water into fresh water is known as desalination. Brackish water treatment can also be done by filtration method. Based on the above background to avoid risks that occur in the use of brackish water in daily life that does not meet the standards of clean water that is safe to use in general and always ensures that the water is still suitable for use, this study designed and built a solenoid valve control system as an automatic valve used for the desalination of ready-to-drink brackish water that is safe and suitable for use in daily life and also has access to monitoring uses the internet of things (IoT) in its operation, so that it can be optimal in monitoring the pH of water and tds in the water as well as the water capacity in the water tank storage in real time by using Arduino uno as a data processor and the esp8266 wifi module for a connection to the internet that will send data to the blynk application. In the design of this device, several sensors were used, such as: pH sensor, tds sensor, and ultrasonic sensor so that it has three outputs, namely water tank storage capacity, water tds value, and water pH placed in the water tank storage to determine the value of the final result in the process of processing brackish water into ready-to-drink water in this study. The results of the work test of this brackish water desalination control system succeeded in removing the color and odor in the water and were able to change the pH level in brackish water from 8.7 pH to 6.43 pH, but the filtered water still tasted salty, so this research still needs to be continued to achieve the standard of drinking water content